2009
DOI: 10.1063/1.3083218
|View full text |Cite
|
Sign up to set email alerts
|

Plasma structures observed in gas breakdown using a 1.5 MW, 110 GHz pulsed gyrotron

Abstract: Regular two-dimensional plasma filamentary arrays have been observed in gas breakdown experiments using a pulsed 1.5 MW, 110 GHz gyrotron. The gyrotron Gaussian output beam is focused to an intensity of up to 4 MW/cm2. The plasma filaments develop in an array with a spacing of about one quarter wavelength, elongated in the electric field direction. The array was imaged using photodiodes, a slow camera, which captures the entire breakdown event, and a fast camera with a 6 ns window. These diagnostics demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 15 publications
8
73
0
Order By: Relevance
“…We can find that the electron number density grows exponentially for all cases, and the growth rates are the same for all situations with identical microwave intensity. Even if the number density of the background electrons is sufficiently low at atmospheric environment and room temperature, the new ionization front is formed on a ns timescale while the experimental studies suggested the front should move to the new one in a ten ns timescale [3]. On the other hand, the influence of the incident microwave intensity is relatively strong on forming the ionization front.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We can find that the electron number density grows exponentially for all cases, and the growth rates are the same for all situations with identical microwave intensity. Even if the number density of the background electrons is sufficiently low at atmospheric environment and room temperature, the new ionization front is formed on a ns timescale while the experimental studies suggested the front should move to the new one in a ten ns timescale [3]. On the other hand, the influence of the incident microwave intensity is relatively strong on forming the ionization front.…”
Section: Resultsmentioning
confidence: 97%
“…Any relationship hence may exist between the formation of the filamentary structures and the thrust. Additionally, another experiment has shown clear formation of regular filamentary plasma arrays propagating toward the microwave source [3].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum intensity of the incident field E y is fixed at 5 MV/m, and the microwave frequency is 110 GHz following Hidaka's experiments [6]. The 1D simulation domain has 2.25λ (the microwave wavelength is λ = 0.27 cm), and the number of grid points used is 40,000 in order to resolve the Debye length of the electrons.…”
Section: Fdtd and Pic-mcc Coupling Simulationmentioning
confidence: 99%
“…Pressure dependencies of the breakdown structure and the thrust performance of a microwave rocket were assessed previously by placing a parabolic thruster in a vacuum chamber [2,3,6]. A discrete plasma was formed at atmospheric pressure because a standing wave was induced in front of the plasma due to waves reflected by the overcritical plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation